TRANSPARANSI PENYALURAN DANA UMKM BUMDES (ANALISIS MANAJEMEN KEUANGAN SYARIAH) Studi di Desa Kaiyasa, Kec. Oba Utara, Provinsi Maluku Utara - Riky Soleman (JURNAL AL-IQTISHAD, 2022)
This study discusses the transparency of MSME funds in Village-Owned Enterprises in Kaiyasa Village, North Oba District, analysis of Islamic financial management. The type of research used is descriptive qualitative field research. The results of this study indicate that the BUMDes in Kaiyasa Village distribution of MSME funds to the Akemafu Village-Owned Enterprises has been carried out in a transparent manner. BUMDes akemafu also experienced ups and downs which resulted in a lack of community participation, so that what had been programmed by the village government was not realized, as well as a lack of human resources or involvement of the management in managing. There are several businesses that are trying to be developed but only become plans. From this aspect, what needs to be improved is the organizational structure of the management, and aspects of its management. The manager emphasized that every MSME administrator and actor made written rules, for example, a structure board which contained information on implementing the values of Islamic principles, namely the principles of honesty, justice, balance, so that they apply according to the rules set, even if they violate these rules, they will be subject to a fine. . And regulate the structure of BUMDes with existing human resources according to their knowledge, and enforce the rules that apply to the management